Exchange Rate and Macroeconomic Performance in Nigeria: A Causal Post Structural Adjustment Programme Investigation (Global Journal of Management and Business Research, 2014)
This paper investigates the causal relationship between exchange rate, balance of payment, external debt, external reserves, gross domestic product growth rate and inflation rate in Nigeria post Structural Adjustment Programme (SAP). Annual time series data 1987-2011 were used as the research sample period. The data were sourced from CBN Statistical Bulletin and Annual Reports of various years. We applied the ADF and PP unit root tests to check the stationarity of the variables. Gross domestic product growth rate and external reserve were stationary at both levels I (0) and I (1). The Johansen cointegration test, equation estimation and Granger causality tests were applied. Johansen cointegration result shows that there exists a long-run equilibrium relationship among the indicators. The Granger causality test between the dependent and independent variables shows a unidirectional causality from exchange rate to BOP, external reserves and gross domestic product growth rate. The independent variables indicate a unidirectional causality from gross domestic product growth rate to external reserve.
Keywords: Exchange Rate; Macroeconomic Indicators; Cointegration